From the discursive subject to the subject of action - Torres-Victoria, Liliana Patricia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
The purpose of this article is to demonstrate that there is no disconnection between the discursive subject and the subject of action. The subject is not the rational, autonomous and transparent antecedent of the action but it is rather built in the action. The subject is constructed by the dialectical relationship between discourse-action/action-discourse, and this consideration places the issue in the political field, as a historical and contingent subject. In order to achieve the purpose of this study, initially there will be an analysis about the discourse and the constitution of the subject. Secondly, there will be an analysis of the relationship between discourse and action, and finally,social and political practices are considered as a process and as a product of the subject of action.